2019
DOI: 10.1111/jpm.12568
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish version of the Psychiatric/Mental health clinical placement survey and an assessment of Spanish student attitudes towards mental health

Abstract: Accessible summary What is known on the subject? The Psychiatric/Mental Health Clinical Placement Survey preplacement, validated in English and widely used, assesses nursing student attitudes towards the mental health field. There are no validated scales in Spanish to assess students' attitudes towards mental health, nor is there evidence of attitudes in Spanish students. What does this article add to existing knowledge? The present study was the first to address the validity of a scale which evaluates n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Based on review of related literature conducted after data had been gathered, feelings nursing students experienced during mental health care were explored. Juliá-Sanchis et al (2019), suggested that the way nursing students feel toward mental health is important because of their potential detrimental influence to their behavior and quality of care as future nursing professionals. For example, in Canada, nursing students decided not to choose mental health nursing as a career due to their negative practicum experiences related to witnessing harmful nursing practices and institutional environments of inpatient psychiatric settings (Slemon et al, 2020) but Rodriguez-Almagro et al (2019) found that among students who had experienced mental health training and who had family members with mental health problems had possessed lower mental health stigma levels than their counterparts who had not had these opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Based on review of related literature conducted after data had been gathered, feelings nursing students experienced during mental health care were explored. Juliá-Sanchis et al (2019), suggested that the way nursing students feel toward mental health is important because of their potential detrimental influence to their behavior and quality of care as future nursing professionals. For example, in Canada, nursing students decided not to choose mental health nursing as a career due to their negative practicum experiences related to witnessing harmful nursing practices and institutional environments of inpatient psychiatric settings (Slemon et al, 2020) but Rodriguez-Almagro et al (2019) found that among students who had experienced mental health training and who had family members with mental health problems had possessed lower mental health stigma levels than their counterparts who had not had these opportunities.…”
Section: Introductionmentioning
confidence: 99%